Public Drug Coverage and Its Impact on Triptan Use Across Canada: A Population‐Based Study. (7th March 2015) - Amadio, Anthony; Lee, Kathy; Yao, Zhan; Camacho, Ximena; Knowles, Sandra; Lay, Christine; Paterson, J. Michael; Hunt, Jordan; Gomes, Tara; ,
Abstract : Background: Public drug coverage for triptan medications varies across jurisdictions in Canada, which may lead to differences in usage patterns and patient risk for medication overuse headache. Methods: We conducted a population‐based, cross‐sectional analysis of publicly funded triptan use in seven provinces across Canada from January 1, 2012 to December 31, 2012. All patients who had filled at least one prescription for a triptan during the study period were included. We defined quantity limits of 6, 12, and 18 triptan units per month to assess the prevalence of high volumes of triptan use, which may place patients at risk for medication overuse headaches, and compared this prevalence between provinces with different funding restrictions. Results: We identified 14, 085 publicly funded users of triptans in 2012 in the seven provinces studied, 82.5% of whom were aged less than 65 years (N = 11, 631). The prevalence of triptan use ranged substantially by province, from 0.04% in Ontario to a maximum of 1.0% in Manitoba ( P  < .001). Furthermore, the percentage of patients in each province using more than 6, 12, or 18 units per month differed significantly between provinces ( P  < .001). In particular, the percentage of patients treated with more than 6 units per month ranged from as low as 2.1% in Saskatchewan to 43.8% in Ontario. Conclusions: Differing public drug reimbursement criteria for triptans may be one contributing factor that has led to our observation of considerable variation in both prevalence of triptan prescribing and potential overuse of these medications. We offer that monthly quantity limits may be considered as a tool to decrease risks for medication overuse headache.